In-line six-mode fiber filter based millimeter-wave generation in tunable and switchable dual wavelength fiber laser for 5G networks - Ahmad, Harith; Lohano, Leela Wanti; Nizamani, Bilal; Samion, Muhamad Zharif; Thambiratnam, Kavintheran; Ismail, Mohamad Faizal (Institute of Physics, 2025)
This work introduces an innovative method for generating high-frequency signals using a dual-wavelength erbium-doped fiber laser (DWEDFL) operating at the C-band. A key innovation in the proposed work is the integration of 1.8 m of six-mode fiber as a compact and novel in-line comb-like wavelength filter, which provides a free spectral range (FSR) of 0.41 nm, offering a unique approach to generate dual-wavelength signals. The DWEDFL operates at wavelengths of 1529.83 and 1530.24 nm, with an optical-signal-to-noise ratio (OSNR) of 56 dB, and provides a broad tunability range of 42 nm. Furthermore, by increasing the length of the six-mode fiber, the DWEDFL achieved a tunable FSR of 0.37 to 0.16 nm. The dual-wavelength laser at tunable FSR generates a tunable radio frequency (RF) signal by utilizing the phenomenon of heterodyne mixing. The novelty of this work lies in the combination of the unique six-mode fiber filter design and its ability to control the FSR, providing beat frequencies that align with the operating bands of 5G networks. The proposed approach demonstrates beat frequencies at 20.50, 26.91, 47.42, and 52.54 GHz, indicating the high-band region (24 to 52 GHz) of the 5G spectrum. To the authors’ knowledge, this method for generating high-frequency signals holds significant potential for driving advancements in 5G applications. © 2025 The Author(s). Published by IOP Publishing Ltd.